Smart Economy untuk Mencapai Ketahanan Ekonomi dan City Branding pada Masa Pandemi Covid-19 di Kabupaten Kendal - Dessy Mayasari (Ekonomis: Journal of Economics and Business, 2023)
Many efforts and strategies have been carried out in maintaining the sustainability of the existence of the economy in Kendal Regency. The main realization is encouraging the development of smart cities as an effort to answer the various problems that are being faced by the Kendal Regency government. For three years, the smart economy dimension has become the focus in realizing Kendal Regency is pro to investment with a percentage reaching 76.25 percent compared to other dimensions. The smart eeconomy criteria applied in Kendal Regency shows that the indicator of innovative spirit is very strong, reaching a score of 94 (11.28%). This innovative spirit emphasizes the innovation spirit of the Kendal Regency government to find newer approaches to economic activities. productivity indicator obtained a score of 76 (9, 12%). The productivity indicator explains the increasing number of people who get jobs accompanied by an increase in income. This condition has been supported by micro and medium enterprises that have been connected to digital platforms, an increase of 12.8% or around 1501 during the Covid-19 pandemic. This condition requires that a product must display characteristics that encourage increased city branding, therefore business actors must be able to partner with various stakeholders to display creative digital content during this.